Baroreflex Sensitivity Predicts Response to Metoprolol in Children With Vasovagal Syncope: A Pilot Study - Tao, Chunyan; Li, Xueying; Tang, Chaoshu; Jin, Hongfang; Du, Junbao (Frontiers in Neuroscience, 2019)
Objective: To explore the role of baroreflex sensitivity (BRS) in head-up tilt test in predicting the therapeutic response of vasovagal syncope (VVS) patients to metoprolol. Materials and Methods: VVS patients treated by metoprolol were enrolled in this study and they were classified as responders and non-responders according to the changes in symptom scores before and after metoprolol treatment. Values of BRS at supine and at positive response occurrence in head-up tilt test were obtained and BRS changes from supine to positive response occurrence were calculated. Differences between responders and non-responders were analyzed. The receiver operating characteristic curve analysis was performed to assess the values of BRS in predicting the therapeutic efficacy of metoprolol in pediatric patients with VVS. Results: Forty patients (14 boys; 11.8 ± 2.5 years) diagnosed with VVS were recruited in the study, 28 of whom were verified as responders to metoprolol and the other 12 patients as non-responders. They did not show any differences in baseline characteristics and hemodynamics in head-up tilt test (p > 0.05). However, the responders had an obviously increased supine BRS value compared to the non-responders (16.9  7.7 ms/mmHg vs 7.6  3.8 ms/mmHg; p < 0.01). No difference in BRS at positive response occurrence was observed between the two groups (8.9  8.5 ms/mmHg vs 10.6  9.8 ms/mmHg; p > 0.05). Accordingly, the changes in BRS of responders were more obvious than that of non-responders (8.0  7.8 ms/mmHg vs -3.0  10.4 ms/mmHg; p < 0.01). The area under the receiver operating characteristic curve for the predictive value of supine BRS was 0.887 (95% CI, 0.7790.995; p < 0.01). A cut-off value of 10 ms/mmHg yielded a sensitivity and specificity of 82% and 83% respectively in predicting therapeutic efficacy of metoprolol in pediatric VVS patients. The area under the receiver operating characteristic curve for the predictive value of BRS changes was 0.827 (95% CI, 0.6930.962; p < 0.01). A cut-off value of 4 ms/mmHg yielded a sensitivity and specificity of 71% and 83%, respectively. Conclusion: BRS may predict the response of children with VVS to metoprolol.